Synergistic film of photovoltaic module as well as preparation method and application of synergistic film
By using mesoporous composite materials and nanomaterials to enhance the ultraviolet reflectivity and interface adhesion performance in photovoltaic modules, the problems of low reflectivity and insufficient adhesion in the existing reflective films are solved. Improve the power generation efficiency and reliability of photovoltaic modules.
Patent Information
- Application Number
- CN202411247461.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The reflectivity of the existing reflective films is difficult to improve in the ultraviolet region, and the adhesion between the aluminum-plated layer and the substrate layer is weak, which affects the service life of the photovoltaic module and the power generation efficiency.
Using a photovoltaic module integrated film, including adhesive layer, composite layer and substrate layer, the reflectivity and adhesion performance are improved through the combination of mesoporous composite material and nanomaterial, and the process is simple and cost is reduced.
Improve reflectivity in the ultraviolet region, improve the power generation power of photovoltaic modules, and enhance the interface adhesion performance, extend the service life of photovoltaic modules.
Smart Images

Figure BDA0005031222820000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic modules, and in particular to a photovoltaic module efficiency enhancement film and a preparation method and application thereof. Background Art
[0002] With the growing global demand for renewable energy, photovoltaic technology, as an important component of clean energy, has become a hot topic in industry research in terms of efficiency and reliability. In traditional photovoltaic modules, the performance of the light absorption layer material directly determines the photoelectric conversion efficiency of the photovoltaic cell, while the overall reliability of the module depends on the interface bonding strength and stability between the layers of material.
[0003] Reflective film is the simplest and easiest way to operate. When producing photovoltaic modules, the reflective film can be directly attached to the glass using pasting equipment. It is easy to use and does not require a high-temperature curing process.
[0004] However, the existing reflective film has the following technical problems during use:
[0005] Most of the existing reflective films are aluminum-plated films with a micro-prismatic structure. The production process is relatively complicated and usually requires multiple processes such as gluing, UV curing, evaporation and compounding. The production cost and material cost are relatively high.
[0006] Since most of the existing reflective films are aluminum-plated films with a micro-prismatic structure, the reflectivity is limited by the aluminum-plated material, usually only about 80% at 380-1200nm, and it is difficult to obtain further improvement. This is because most of the existing reflective films are aluminum-plated films with a micro-prismatic structure, and their reflectivity depends largely on the performance of the aluminum-plated layer. Although the reflectivity of aluminum in the ultraviolet region is relatively high, its reflective performance is limited by the characteristics of the material itself at specific wavelengths (such as the short-wave part of ultraviolet rays), and it is difficult to reach a higher level. Although the micro-prismatic structure can effectively enhance the scattering and reflection of light, in the ultraviolet region, the absorption and scattering characteristics of the material to light may change, making it difficult to further improve the reflectivity.
[0007] Moreover, the adhesion between the aluminum coating and the substrate layer is weak. During the long-term aging process of photovoltaic modules, there may be a risk of delamination, which will affect the service life of the photovoltaic modules. Summary of the invention
[0008] In order to solve technical problems such as how to effectively improve the reflectivity in the ultraviolet region and improve the interface adhesion performance to improve the power generation capacity and overall reliability of photovoltaic modules, the present invention proposes a photovoltaic module efficiency enhancement film and its preparation method and application, which has a simple process and not only improves the reflectivity in the ultraviolet region, thereby improving the power generation capacity of the photovoltaic module, but also improves the interface adhesion performance and improves the overall reliability of the photovoltaic module.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] In one aspect, the present invention provides a photovoltaic module efficiency enhancement film, comprising: an adhesive layer, on which a substrate layer and a composite layer are sequentially arranged from bottom to top,
[0011] The composite layer comprises the following components in parts by weight:
[0012] 57-95 parts of propylene polymer alloy;
[0013] 5-40 parts of mesoporous composite material;
[0014] Additives 0.1-3 parts;
[0015] The addition ratio of the propylene polymer in the propylene polymer alloy is greater than 55%;
[0016] The substrate layer comprises the following components in parts by weight:
[0017] 62-95 parts of propylene polymer;
[0018] 5-35 parts of filler;
[0019] Additives 0.1-3 parts;
[0020] The adhesive layer comprises the following components in parts by weight:
[0021] 55-95 parts of bonding resin;
[0022] 5-40 parts of mesoporous composite material;
[0023] Additives 0.1-3 parts;
[0024] Crosslinking agent 0.1-2 parts.
[0025] The present invention proposes a photovoltaic module efficiency enhancement film and a preparation method thereof, which has a simple process and not only improves the reflectivity in the ultraviolet region, thereby improving the power generation power of the photovoltaic module, but also improves the adhesion performance of the interface and improves the overall reliability of the photovoltaic module.
[0026] As an optimal technical solution, the mesoporous composite material is a composite material of mesoporous material and nanomaterial; the mesoporous material is at least one of mesoporous material MCM-41, mesoporous material SBA-15, and mesoporous material MCM-48; the nanomaterial is at least one of nano zinc oxide, nano calcium carbonate, and nano barium sulfate; the particle size of the nanomaterial is 10-200nm.
[0027] As a preferred technical solution, the propylene polymer alloy is an alloy of a propylene polymer and an ethylene polymer; the ethylene polymer is a combination of any one or more of polyethylene, ethylene-octene copolymer, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, maleic anhydride grafted ethylene-butene copolymer, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-hexene copolymer; the propylene polymer is a combination of any one or more of homopolypropylene, copolymer polypropylene, block polypropylene, and random copolymer polypropylene.
[0028] As a preferred technical solution, the bonding resin is an ethylene polymer with a melting point of 65-100°C.
[0029] As a preferred technical solution, the filler is any one or more combinations of titanium dioxide, calcium carbonate, talc, mica, barium sulfate, silicon dioxide, and glass microbeads.
[0030] As a preferred technical solution, the additives include light stabilizers and antioxidants;
[0031] The light stabilizer is composed of a UV absorber and / or a UV stabilizer;
[0032] The antioxidant is a primary antioxidant or is composed of a primary antioxidant and a secondary antioxidant;
[0033] The ultraviolet absorber is any one or more of benzophenone, benzotriazole and triazine ultraviolet absorbers;
[0034] The ultraviolet stabilizer is a hindered amine ultraviolet stabilizer;
[0035] The main antioxidant is a hindered phenol antioxidant or a hindered phenol phosphite synergistic antioxidant;
[0036] The secondary antioxidant is a phosphite or thioester antioxidant.
[0037] As a preferred technical solution, the cross-linking agent is any one or more of diisopropylbenzene oxide, tert-butyl peroxide-2-ethylhexyl carbonate, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-amyl peroxide-2-ethylhexyl carbonate, di(2-ethyl)hexyl peroxydicarbonate, tert-amyl peroxide-2-ethylhexyl carbonate, benzoyl peroxide, tert-butyl peroxide-2-ethylhexyl carbonate, triallyl isocyanurate, 3-(trimethoxysilyl)propyl methacrylate, 3-vinylphenol, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and glycerol trihydroxypropyl ether triacrylate.
[0038] As a preferred technical solution, the thickness of the composite layer is 10-100 um, the thickness of the substrate layer is 40-100 um, and the thickness of the adhesive layer is 10-50 um.
[0039] In another aspect, the present invention provides a method for preparing a photovoltaic module synergistic film, and preparing the photovoltaic module synergistic film as described in any one of the above items, comprising the following preparation steps:
[0040] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, and extruded and granulated at a temperature of 100-220° C. to obtain composite layer particles, substrate layer particles and adhesive layer particles;
[0041] The composite layer particles, the substrate layer particles and the adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module efficiency enhancement film;
[0042] Alternatively, the composite layer particles and the substrate layer particles are extruded through a multi-layer casting machine at a temperature of 130-220°C to form a substrate layer and a composite layer, and then the adhesive layer particles are coated on the substrate layer at a temperature of 100-140°C by coating composite to form an adhesive layer.
[0043] In yet another aspect, use of the efficiency enhancing film of a photovoltaic module according to any one of the above items in a photovoltaic module.
[0044] The invention provides a photovoltaic module synergistic film and a preparation method and application thereof, which have the following beneficial effects:
[0045] 1) The process is simple, which not only improves the reflectivity in the ultraviolet region, thereby increasing the power generation of photovoltaic modules, but also improves the adhesion performance of the interface and improves the overall reliability of photovoltaic modules;
[0046] 2) The adhesive layer is provided with a base material layer and a composite layer from bottom to top, and the materials of the above layers are all thermoplastic materials, which can be formed in one step by a co-extrusion process, and do not contain a high-cost metal reflective layer, so the process cost and material cost are greatly reduced;
[0047] The reflectivity of the UV band of 330-380nm is >50% through compounding of the components of each layer, which improves the reflectivity of the UV region. At the same time, the reflectivity of the visible and near-infrared bands of 380-1100nm can reach more than 90%, thereby obtaining a higher power generation capacity of the photovoltaic modules;
[0048] By utilizing mesoporous composite materials, a higher reflectivity at 330-380nm is achieved. The addition of mesoporous materials improves the adhesion performance of the interface and enhances the overall reliability of photovoltaic modules. DETAILED DESCRIPTION
[0049] The preferred embodiments of the present invention are described in detail below with reference to the embodiments.
[0050] The present invention provides a photovoltaic module efficiency enhancement film, comprising: an adhesive layer, on which a substrate layer and a composite layer are sequentially arranged from bottom to top,
[0051] The composite layer comprises the following components in parts by weight:
[0052] 57-95 parts of propylene polymer alloy;
[0053] 5-40 parts of mesoporous composite material;
[0054] Additives 0.1-3 parts;
[0055] The addition ratio of the propylene polymer in the propylene polymer alloy is greater than 55%;
[0056] The substrate layer comprises the following components in parts by weight:
[0057] 62-95 parts of propylene polymer;
[0058] 5-35 parts of filler;
[0059] Additives 0.1-3 parts;
[0060] The adhesive layer comprises the following components in parts by weight:
[0061] 55-95 parts of bonding resin;
[0062] 5-40 parts of mesoporous composite material;
[0063] Additives 0.1-3 parts;
[0064] Crosslinking agent 0.1-2 parts.
[0065] The present invention proposes a gap enhancement film for a photovoltaic module, which has a simple process and not only improves the reflectivity in the ultraviolet region, thereby improving the power generation of the photovoltaic module, but also improves the adhesion performance of the interface and improves the overall reliability of the photovoltaic module.
[0066] Preferably, the adhesive layer is provided with a substrate layer and a composite layer in order from bottom to top, and the materials of the above layers are all thermoplastic materials, which can be formed in one step by a co-extrusion process, and do not contain a high-cost metal reflective layer, so the process cost and material cost are greatly reduced;
[0067] Preferably, the reflectivity of the ultraviolet band of 330-380nm is >50% by compounding the components of each layer, thereby improving the reflectivity of the ultraviolet region, and at the same time, the reflectivity of the visible and near-infrared bands of 380-1100nm can reach more than 90%, thereby obtaining a higher photovoltaic module power generation capacity;
[0068] Preferably, a higher reflectivity at 330-380 nm is achieved by using a mesoporous composite material, and the addition of the mesoporous material improves the adhesion performance of the interface and enhances the overall reliability of the photovoltaic module.
[0069] Preferably, the mesoporous composite material is a composite material of a mesoporous material and a nanomaterial; the mesoporous material is at least one of mesoporous material MCM-41, mesoporous material SBA-15, and mesoporous material MCM-48; the nanomaterial is at least one of nano zinc oxide, nano calcium carbonate, and nano barium sulfate; the particle size of the nanomaterial is 10-200nm; with the development of battery technology, double-sided TOPCon batteries have had a high response to light in the near-ultraviolet region of 330-380nm. General reflective materials such as titanium dioxide are difficult to reflect this part of the light. The preferred mesoporous material in this application achieves a higher reflectivity at 330-380nm; at the same time, the addition of mesoporous materials improves the interfacial adhesion of the materials.
[0070] Preferably, the propylene polymer alloy is an alloy of a propylene polymer and an ethylene polymer; the ethylene polymer is a combination of any one or more of polyethylene, ethylene-octene copolymer, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, maleic anhydride grafted ethylene-butene copolymer, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-hexene copolymer.
[0071] Preferably, the bonding resin is an ethylene polymer with a melting point of 65-100°C.
[0072] Preferably, the propylene-based polymer is any one or more combinations of homopolypropylene, copolymer polypropylene, block polypropylene and random copolymer polypropylene.
[0073] Preferably, the filler is any one or more combinations of titanium dioxide, calcium carbonate, talc, mica, barium sulfate, silicon dioxide, and glass microspheres.
[0074] Preferably, the additives include light stabilizers and antioxidants;
[0075] Preferably, the light stabilizer consists of a UV absorber and / or a UV stabilizer;
[0076] Preferably, the antioxidant is a primary antioxidant or consists of a primary antioxidant and a secondary antioxidant;
[0077] Preferably, the ultraviolet absorber is any one or more of benzophenone, benzotriazole and triazine ultraviolet absorbers;
[0078] Preferably, the UV stabilizer is a hindered amine UV stabilizer;
[0079] Preferably, the primary antioxidant is a hindered phenol antioxidant or a hindered phenol phosphite synergistic antioxidant;
[0080] Preferably, the secondary antioxidant is a phosphite or thioester antioxidant.
[0081] Preferably, the crosslinking agent is any one or more of diisopropylbenzene oxide, tert-butyl peroxy-2-ethylhexyl carbonate, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-amyl peroxy-2-ethylhexyl carbonate, di(2-ethyl)hexyl peroxydicarbonate, tert-amyl peroxy-2-ethylhexyl carbonate, benzoyl peroxide, tert-butyl peroxy-2-ethylhexyl carbonate, triallyl isocyanurate, 3-(trimethoxysilyl)propyl methacrylate, 3-vinylphenol, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and glycerol trihydroxypropyl ether triacrylate.
[0082] Preferably, the thickness of the composite layer is 10-100 um, the thickness of the substrate layer is 40-100 um, and the thickness of the adhesive layer is 10-50 um.
[0083] The present invention provides a method for preparing a photovoltaic module synergistic film, and the method for preparing the photovoltaic module synergistic film as described in any one of the above items comprises the following preparation steps:
[0084] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, and extruded and granulated at a temperature of 100-220° C. to obtain composite layer particles, substrate layer particles and adhesive layer particles;
[0085] The composite layer particles, the substrate layer particles and the adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module efficiency enhancement film;
[0086] Alternatively, the composite layer particles and the substrate layer particles are extruded through a multi-layer casting machine at a temperature of 130-220°C to form a substrate layer and a composite layer, and then the adhesive layer particles are coated on the substrate layer at a temperature of 100-140°C by coating composite to form an adhesive layer.
[0087] The present invention provides a method for preparing a photovoltaic module synergistic film, which has a simple process and not only improves the reflectivity in the ultraviolet region, thereby improving the power generation of the photovoltaic module, but also improves the adhesion performance of the interface and improves the overall reliability of the photovoltaic module.
[0088] The application of the photovoltaic module efficiency enhancement film according to any of the above items in the photovoltaic module not only improves the power generation capacity of the photovoltaic module, but also improves the overall reliability of the photovoltaic module.
[0089] Example 1
[0090] The present invention provides a method for preparing a photovoltaic module synergistic film, comprising the following preparation steps:
[0091] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, wherein the composite layer particles are extruded and granulated at a temperature of 200°C, and dried for use; the substrate layer particles are extruded and granulated at a temperature of 220°C, and dried for use; the adhesive layer particles are extruded and granulated at a temperature of 120°C, and dried for use.
[0092] The composite layer particles, substrate layer particles and adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module enhancement film; the thickness of each layer of the photovoltaic module enhancement film is: the composite layer is 30um thick, the substrate layer is 60um thick, and the adhesive layer is 30um thick;
[0093] Wherein, the raw materials for preparing the composite layer include:
[0094] 79.4 parts of propylene polymer alloy (comprising 40 parts of propylene polymer copolymer polypropylene and 29.4 parts of ethylene polymer polyethylene), 20 parts of a composite material of mesoporous material SBA-15 and nano-barium sulfate, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0095] The raw materials for preparing the substrate layer include:
[0096] 74.4 parts of propylene copolymer polypropylene, 25 parts of filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0097] The bonding layer preparation raw materials include:
[0098] 98.7 parts of bonding resin ethylene-vinyl acetate copolymer, 15 parts of a composite material of mesoporous material SBA-15 and nano-barium sulfate, 0.1 parts of antioxidant 1076, 0.3 parts of light stabilizer 770, 0.3 parts of cross-linking agent tert-amyl peroxide 2-ethylhexyl carbonate, 0.2 parts of triallyl isocyanurate;
[0099] The weight ratio of the mesoporous material SBA-15 to the nano-barium sulfate in the composite material of the mesoporous material SBA-15 and the nano-barium sulfate is 1:1.
[0100] The present invention provides a photovoltaic module synergistic film, which is prepared according to the above photovoltaic module synergistic film preparation method, wherein the adhesive layer is provided with a substrate layer and a composite layer in sequence from bottom to top.
[0101] Example 2
[0102] The present invention provides a method for preparing a photovoltaic module synergistic film, comprising the following preparation steps:
[0103] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, wherein the composite layer particles are extruded and granulated at a temperature of 200°C, and dried for use; the substrate layer particles are extruded and granulated at a temperature of 220°C, and dried for use; the adhesive layer particles are extruded and granulated at a temperature of 120°C, and dried for use.
[0104] The composite layer particles, substrate layer particles and adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module enhancement film; the thickness of each layer of the photovoltaic module enhancement film is: the composite layer is 30um thick, the substrate layer is 60um thick, and the adhesive layer is 30um thick;
[0105] Wherein, the raw materials for preparing the composite layer include:
[0106] 69.4 parts of propylene polymer alloy (comprising 40 parts of propylene polymer copolymer polypropylene and 29.4 parts of ethylene polymer polyethylene), 30 parts of a composite material of mesoporous material MCM-48 and nano-calcium carbonate, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0107] The raw materials for preparing the substrate layer include:
[0108] 74.4 parts of propylene copolymer polypropylene, 25 parts of filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0109] The bonding layer preparation raw materials include:
[0110] 98.7 parts of bonding resin ethylene-vinyl acetate copolymer, 15 parts of a composite material of mesoporous material MCM-48 and nano calcium carbonate, 0.1 parts of antioxidant 1076, 0.3 parts of light stabilizer 770, 0.3 parts of cross-linking agent peroxidized 2-ethylhexyl carbonate tert-amyl, 0.2 parts of triallyl isocyanurate;
[0111] The weight ratio of the mesoporous material MCM-48 to the nano-calcium carbonate in the composite material of the mesoporous material MCM-48 and the nano-calcium carbonate is 1:1.
[0112] The present invention provides a photovoltaic module synergistic film, which is prepared according to the above photovoltaic module synergistic film preparation method, wherein the adhesive layer is provided with a substrate layer and a composite layer in sequence from bottom to top.
[0113] Example 3
[0114] The present invention provides a method for preparing a photovoltaic module synergistic film, comprising the following preparation steps:
[0115] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, wherein the composite layer particles are extruded and granulated at a temperature of 200°C, and dried for use; the substrate layer particles are extruded and granulated at a temperature of 220°C, and dried for use; the adhesive layer particles are extruded and granulated at a temperature of 120°C, and dried for use.
[0116] The composite layer particles, substrate layer particles and adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module enhancement film; the thickness of each layer in the photovoltaic module enhancement film is: the composite layer thickness is 30um, the substrate layer thickness is 60um, and the adhesive layer thickness is 30um;
[0117] Wherein, the raw materials for preparing the composite layer include:
[0118] 84.4 parts of propylene polymer alloy (comprising 40 parts of propylene polymer copolymer polypropylene and 29.4 parts of ethylene polymer polyethylene), 15 parts of a composite material of mesoporous material MCM-41 and nano zinc oxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0119] The raw materials for preparing the substrate layer include:
[0120] 74.4 parts of propylene polymer copolymer polypropylene, 25 parts of filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020.
[0121] The bonding layer preparation raw materials include:
[0122] 98.7 parts of bonding resin ethylene-vinyl acetate copolymer, 15 parts of a composite material of mesoporous material MCM-41 and nano zinc oxide, 0.1 parts of antioxidant 1076, 0.3 parts of light stabilizer 770, 0.3 parts of cross-linking agent tert-amyl peroxide 2-ethylhexyl carbonate, and 0.2 parts of triallyl isocyanurate.
[0123] The weight ratio of the mesoporous material MCM-41 and the nano-zinc oxide in the composite material of the mesoporous material MCM-41 and the nano-zinc oxide is 1:1.
[0124] The present invention provides a photovoltaic module synergistic film, which is prepared according to the above photovoltaic module synergistic film preparation method, wherein the adhesive layer is provided with a substrate layer and a composite layer in sequence from bottom to top.
[0125] Comparative Example 1
[0126] Comparative Example 1 provides a method for preparing a photovoltaic module efficiency enhancement film, comprising the following preparation steps:
[0127] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, wherein the composite layer particles are extruded and granulated at a temperature of 200°C, and dried for use; the substrate layer particles are extruded and granulated at a temperature of 220°C, and dried for use; the adhesive layer particles are extruded and granulated at a temperature of 120°C, and dried for use.
[0128] The composite layer particles, substrate layer particles and adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module enhancement film; the thickness of each layer of the photovoltaic module enhancement film is: the composite layer is 30um thick, the substrate layer is 60um thick, and the adhesive layer is 30um thick;
[0129] Among them, the raw materials for preparing the composite layer include:
[0130] 69.4 parts of propylene polymer alloy (comprising 40 parts of propylene polymer copolymer polypropylene and 29.4 parts of ethylene polymer polyethylene), 30 parts of mesoporous material MCM-48, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0131] The raw materials for preparing the substrate layer include:
[0132] 74.4 parts of propylene copolymer polypropylene, 25 parts of filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0133] The raw materials for preparing the bonding layer include:
[0134] 98.7 parts of bonding resin ethylene-vinyl acetate copolymer, 15 parts of mesoporous material MCM-48, 0.1 parts of antioxidant 1076, 0.3 parts of light stabilizer 770, 0.3 parts of crosslinking agent peroxy 2-ethylhexyl carbonate tert-amyl ester, 0.2 parts of triallyl isocyanurate;
[0135] Comparative Example 1 provides a photovoltaic module efficiency enhancement film, which is prepared according to the above method for preparing the photovoltaic module efficiency enhancement film, wherein the adhesive layer is provided with a substrate layer and a composite layer in sequence from bottom to top.
[0136] Comparative Example 2
[0137] Comparative Example 2 provides a method for preparing a photovoltaic module efficiency enhancement film, comprising the following preparation steps:
[0138] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, wherein the composite layer particles are extruded and granulated at a temperature of 200°C, and dried for use; the substrate layer particles are extruded and granulated at a temperature of 220°C, and dried for use; the adhesive layer particles are extruded and granulated at a temperature of 120°C, and dried for use.
[0139] The composite layer particles, substrate layer particles and adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module enhancement film; the thickness of each layer in the photovoltaic module enhancement film is: the composite layer is 30um thick, the substrate layer is 60um thick, and the adhesive layer is 30um thick;
[0140] Among them, the raw materials for preparing the composite layer include:
[0141] 69.4 parts of propylene polymer alloy (comprising 40 parts of propylene polymer copolymer polypropylene and 29.4 parts of ethylene polymer polyethylene), 30 parts of nano barium sulfate, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0142] The raw materials for preparing the substrate layer include:
[0143] 74.4 parts of propylene polymer copolymer polypropylene, 25 parts of filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020.
[0144] The raw materials for preparing the bonding layer include:
[0145] 98.7 parts of bonding resin ethylene-vinyl acetate copolymer, 15 parts of nano barium sulfate, 0.1 parts of antioxidant 1076, 0.3 parts of light stabilizer 770, 0.3 parts of cross-linking agent peroxidized 2-ethylhexyl carbonate tert-amyl, and 0.2 parts of triallyl isocyanurate.
[0146] Comparative Example 2 provides a photovoltaic module efficiency enhancement film, which is prepared according to the above method for preparing the photovoltaic module efficiency enhancement film, wherein the adhesive layer is provided with a substrate layer and a composite layer in sequence from bottom to top.
[0147] Comparative Example 3
[0148] Comparative Example 3 provides a method for preparing a photovoltaic module efficiency enhancement film, comprising the following preparation steps:
[0149] The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, wherein the composite layer particles are extruded and granulated at a temperature of 200°C, and dried for use; the substrate layer particles are extruded and granulated at a temperature of 220°C, and dried for use; the adhesive layer particles are extruded and granulated at a temperature of 120°C, and dried for use.
[0150] The composite layer particles, substrate layer particles and adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module enhancement film; the thickness of each layer of the photovoltaic module enhancement film is: the composite layer is 30um thick, the substrate layer is 60um thick, and the adhesive layer is 30um thick;
[0151] Among them, the raw materials for preparing the composite layer include:
[0152] 69.4 parts of propylene polymer alloy (including 40 parts of propylene polymer copolymer polypropylene and 29.4 parts of ethylene polymer polyethylene), 30 parts of filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0153] The raw materials for preparing the substrate layer include:
[0154] 74.4 parts of propylene copolymer polypropylene, 25 parts of filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020;
[0155] The raw materials for preparing the bonding layer include:
[0156] 98.7 parts of bonding resin ethylene-vinyl acetate copolymer, 15 parts of filler titanium dioxide, 0.1 parts of antioxidant 1076, 0.3 parts of light stabilizer 770, 0.3 parts of cross-linking agent peroxidized 2-ethylhexyl carbonate tert-amyl, and 0.2 parts of triallyl isocyanurate.
[0157] Comparative Example 3 provides a photovoltaic module efficiency enhancement film, which is prepared according to the above method for preparing the photovoltaic module efficiency enhancement film, wherein the adhesive layer is provided with a substrate layer and a composite layer in sequence from bottom to top.
[0158] Experimental means of experimental data testing
[0159] The following tests were performed on Examples 1-3 and Comparative Examples 1-3:
[0160] The reflectivity is tested according to IEC62788-2-1, and the test band is 330-1100nm (330-380nm and 380-1100nm are distinguished).
[0161] The adhesion test method between the composite layer and the film is as follows: cut the sample into small strips with a width of 1 cm, stack them in the order of synergistic film (composite layer with film surface) / release paper / film / glass, put them into a laminator for lamination, the lamination temperature is 120°C for one chamber and 140°C for the second chamber, the lamination time is 18 minutes, and after lamination, a tensile tester is used to test the peel strength between the composite layer and the film.
[0162] The adhesion test method between the adhesive layer and the glass is as follows: cut the sample into small strips with a width of 1 cm, stack them in the order of synergistic film (adhesive layer attached to the glass surface) / release paper / glass, put them into a laminator for lamination, the lamination temperature is 120°C for one chamber and 140°C for the second chamber, the lamination time is 18 minutes, and after lamination, a tensile tester is used to test the peel strength of the composite layer and the film.
[0163] The samples of Examples 1-3 and Comparative Examples 1-3 were cut into 0.5 cm strips, heated to 120° C. by a film laminating machine and attached to glass (between cells and between strings). With other materials unchanged, photovoltaic modules were prepared and their power was tested.
[0164] The experimental data test results are shown in Table 1.
[0165] Table 1 Test experimental data
[0166]
[0167] From the data in Table 1, we can see that:
[0168] The reflectivity of the synergistic films of the photovoltaic modules provided in Examples 1-3 in the ultraviolet region of 330-380nm is as high as over 50%, which is higher than that of Comparative Example 1 in which both the composite layer and the bonding layer do not contain nanomaterials and Comparative Example 2 in which both the composite layer and the bonding layer do not contain mesoporous materials, indicating that the combination of mesoporous materials and nanomaterials can improve the reflectivity in the ultraviolet region. The film provided in Comparative Example 3 does not contain mesoporous materials and nanomaterials, so the reflectivity in the ultraviolet region of 330-380nm is as low as 6.84%, which is basically no reflectivity.
[0169] The reflectivity of the photovoltaic modules provided by Examples 1-3 and Comparative Examples 1-3 in the visible and near-infrared regions of 380-1100 nm is substantially the same, indicating that the composite of the mesoporous material and the nanomaterial in the examples will not affect the reflectivity in this band.
[0170] The adhesion between the composite layer of the synergistic film of the photovoltaic module provided in Examples 1-3 and Comparative Example 1 and the adhesive film is as high as 33 N / cm or more, but the adhesion between the composite layer of the synergistic film of the photovoltaic module provided in Comparative Example 2-3 and the adhesive film is reduced to below 14 N / cm. This is because no mesoporous material is added to the composite layer of the synergistic film of the photovoltaic module provided in Comparative Example 2-3. The adhesion between the adhesive layer of the synergistic film of the photovoltaic module provided in Examples 1-3 and Comparative Example 1 and the glass is as high as 63 N / cm or more, but the adhesion between the adhesive layer of the synergistic film of the photovoltaic module provided in Comparative Example 2-3 and the glass is reduced to below 47 N / cm. This is because no mesoporous material is added to the adhesive layer of the synergistic film of the photovoltaic module provided in Comparative Example 2-3. Therefore, we can see from Table 1 that the addition of mesoporous materials to the composite layer and adhesive layer of the synergistic film of the photovoltaic module provided in the present application can improve the interface adhesion performance.
[0171] The power comparison is positively correlated with the reflectivity. The power of the photovoltaic module enhancement films provided in Examples 1-3 when used in photovoltaic modules is higher than the power of the photovoltaic module enhancement films provided in Comparative Examples 1-3 when used in photovoltaic modules, especially higher than Comparative Example 3, indicating that the composite of mesoporous material and nanomaterial in the photovoltaic module enhancement film provided in the present application not only improves the reflectivity in the ultraviolet region, thereby improving the power generation of the photovoltaic module, but also improves the adhesion performance of the interface, thereby improving the overall reliability of the photovoltaic module.
[0172] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all various changes or equivalent substitutions falling within the scope of the claims of the present application are included. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present invention.
Claims
1. A photovoltaic module efficiency enhancement film, characterized in that: include: The adhesive layer includes a substrate layer and a composite layer in sequence from bottom to top. The composite layer comprises the following components in parts by weight: 57-95 parts of propylene polymer alloy; 5-40 parts of mesoporous composite material; Additives 0.1-3 parts; The addition ratio of the propylene polymer in the propylene polymer alloy is greater than 55%; The substrate layer comprises the following components in parts by weight: 62-95 parts of propylene polymer; 5-35 parts of filler; Additives 0.1-3 parts; The adhesive layer comprises the following components in parts by weight: 55-95 parts of bonding resin; 5-40 parts of mesoporous composite material; Additives 0.1-3 parts; Crosslinking agent 0.1-2 parts.
2. The photovoltaic module efficiency enhancement film according to claim 1, characterized in that: The mesoporous composite material is a composite material of a mesoporous material and a nanomaterial; the mesoporous material is at least one of mesoporous material MCM-41, mesoporous material SBA-15, and mesoporous material MCM-48; the nanomaterial is at least one of nano zinc oxide, nano calcium carbonate, and nano barium sulfate; the particle size of the nanomaterial is 10-200nm.
3. The photovoltaic module efficiency enhancement film according to claim 1, characterized in that: The propylene polymer alloy is an alloy of a propylene polymer and an ethylene polymer; the ethylene polymer is a combination of any one or more of polyethylene, ethylene-octene copolymer, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, maleic anhydride grafted ethylene-butene copolymer, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-hexene copolymer; the propylene polymer is a combination of any one or more of homopolypropylene, copolymer polypropylene, block polypropylene, and random copolymer polypropylene.
4. The photovoltaic module efficiency enhancement film according to claim 1, characterized in that: The bonding resin is an ethylene polymer with a melting point of 65-100°C.
5. The photovoltaic module efficiency enhancement film according to any one of claims 1, characterized in that: The filler is any one or more combinations of titanium dioxide, calcium carbonate, talc, mica, barium sulfate, silicon dioxide, and glass microbeads.
6. The photovoltaic module efficiency enhancement film according to claim 1, characterized in that: The additives include light stabilizers and antioxidants; The light stabilizer is composed of a UV absorber and / or a UV stabilizer; The antioxidant is a primary antioxidant or is composed of a primary antioxidant and a secondary antioxidant; The ultraviolet absorber is any one or more of benzophenone, benzotriazole and triazine ultraviolet absorbers; The ultraviolet stabilizer is a hindered amine ultraviolet stabilizer; The main antioxidant is a hindered phenol antioxidant or a hindered phenol phosphite synergistic antioxidant; The secondary antioxidant is a phosphite or thioester antioxidant.
7. The photovoltaic module efficiency enhancement film according to claim 1, characterized in that: The crosslinking agent is any one or more of diisopropylbenzene oxide, tert-butyl peroxide-2-ethylhexyl carbonate, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-amyl peroxide-2-ethylhexyl carbonate, di(2-ethyl)hexyl peroxydicarbonate, tert-amyl peroxide-2-ethylhexyl carbonate, benzoyl peroxide, tert-butyl peroxide-2-ethylhexanoate, triallyl isocyanurate, 3-(trimethoxysilyl)propyl methacrylate, 3-vinylphenol, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and glycerol trihydroxypropyl ether triacrylate.
8. The photovoltaic module efficiency enhancement film according to claim 1, characterized in that: The thickness of the composite layer is 10-100um, the thickness of the substrate layer is 40-100um, and the thickness of the adhesive layer is 10-50um.
9. A method for preparing a photovoltaic module synergistic film, characterized in that: The preparation of the photovoltaic module efficiency enhancement film according to any one of claims 1 to 8 comprises the following preparation steps: The components of the composite layer, the substrate layer and the adhesive layer are mixed according to the weight ratio, and extruded and granulated at a temperature of 100-220° C. to obtain composite layer particles, substrate layer particles and adhesive layer particles; The composite layer particles, the substrate layer particles and the adhesive layer particles are extruded through a multi-layer casting machine to obtain a photovoltaic module efficiency enhancement film; Alternatively, the composite layer particles and the substrate layer particles are extruded through a multi-layer casting machine at a temperature of 130-220°C to form a substrate layer and a composite layer, and then the adhesive layer particles are coated on the substrate layer at a temperature of 100-140°C by coating composite to form an adhesive layer.
10. Use of the photovoltaic module efficiency enhancement film according to any one of claims 1 to 8 in a photovoltaic module.
